Optimization of finger-jointing in rubberwood processing - Ratnasingam, Jegatheswaran; Scholz, Frieder (2009)
The study evaluated the finger-jointing configuration of furniture-grade Rubberwood (Hevea brasiliensis) lumber. It was found that fingers of 15 mm in length using PVAc adhesive produced optimum results in terms of bending strength and process economics. Furthermore, finger jointing contributes to yield improvement in Rubberwood processing and will continue to be widely used in the Rubberwood furniture manufacturing industry.